1997
DOI: 10.1007/s004670050366
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutrition on urinary oxalate and calcium in preterm and term infants

Abstract: Few data for normal urinary oxalate (Ox) and calcium (Ca) excretion related both to gestational age and nutritional factors have been reported in preterm or term infants. We therefore determined the molar Ox and Ca to creatinine (Cr) ratios in spot urines from 64 preterm and 37 term infants aged 1-60 days, either fed formula or human milk (HM). Only vitamin D was supplemented; renal or metabolic diseases were excluded. Urinary Ox/Cr ratio was higher in preterm than in term infants, both when formula fed (1st m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 29 publications
6
25
0
Order By: Relevance
“…Renal calcium excretion was elevated initially (10 mol/mol creatinine) but decreased to 0.77 mol/mol creatinine at 3 months of age (normal values for preterm infants: 0.57ϩ0.41 mol/mol creatinine 27 ). The decline of urinary calcium excretion was independent from indomethacin treatment.…”
Section: Figmentioning
confidence: 98%
“…Renal calcium excretion was elevated initially (10 mol/mol creatinine) but decreased to 0.77 mol/mol creatinine at 3 months of age (normal values for preterm infants: 0.57ϩ0.41 mol/mol creatinine 27 ). The decline of urinary calcium excretion was independent from indomethacin treatment.…”
Section: Figmentioning
confidence: 98%
“…oxalate). Babies receiving parenteral nutrition have a higher oxalate and calcium but lower citrate excretion, contributing to higher calcium oxalate saturation [4]. Urine from premature babies inhibits calcium oxalate crystal agglomeration less well than that from babies born at term, increasing the risk of nephrocalcinosis and stone formation [3].…”
Section: Nephrolithiasis In Ex-premature Childrenmentioning
confidence: 99%
“…Indeed, two recent studies have shown that oxalate excretion in premature neonates depends on the GA as well as the day of life [15,32]. This study is the first to our knowledge that examined urinary oxalate in two groups of preterm infants with different type of feeding for a longer duration than the 1st week of life.…”
Section: Discussionmentioning
confidence: 96%
“…Other risk factors are furosemide treatment [18], steroid treatment, very low BW and gestational age (GA) and complicated perinatal course [19,29,31]. Recent studies have shown that disturbances in the renal excretion of certain factors, which promote or inhibit stone formation, may lead to nephrocalcinosis [15,30]. Such factors are calcium, oxalate (lithogenics), citrate and magnesium (inhibitors) [14,30,32].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation